Adherence to recommended diet among patients with diabetes mellitus type 2 on follow-up at Adama Hospital Medical College, Ethiopia - Abose, Saron; Dassie, Godana Arero; Megerso, Abebe; Charkos, Tesfaye Getachew (Frontiers in Medicine, 2024)
Non-adherence to dietary guidelines is a significant challenge in managing diabetes mellitus and its complications. Its consequences were significantly associated with a deterioration in patients' quality of life and an increased socioeconomic burden on healthcare delivery systems. This study aimed to assess the magnitude of adherence to recommended diet and associated factors among patients with diabetes mellitus type 2 on follow-up care at Adama Hospital Medical College Oromia, Ethiopia. A hospital-based cross-sectional study design was conducted. Participants were selected through systematic random sampling. Data were collected using structured, interviewer-administered questionnaires. The perceived dietary adherence questionnaire was used to assess the level of dietary adherence. A simple binary logistic regression was used to identify candidate variables, while a multivariable logistic regression assessed factors associated with adherence to the recommended diet. A p-value < 0.05 were considered as statistically significant. All analyses were performed using SPSS and R programming software. A total of 405 participants were included in the study, with a response rate of 96.2%. The magnitude of non-adherence to the recommended diet was 64.2%. In in this study, high glycemic level, food insecure, poor diabetic knowledge and low perceived susceptibility were significantly associated factors for non-adherence to recommended diet among patients with diabetes mellitus type 2. An integrated approach that combines socioeconomic support, nutritional guidance, and risk awareness may greatly enhance dietary adherence and optimize diabetes management.